2017
DOI: 10.1186/s12913-017-2511-x
|View full text |Cite
|
Sign up to set email alerts
|

Using mobile phones to ensure that referred tuberculosis patients reach their treatment facilities: a call that makes a difference

Abstract: BackgroundOver the last decade, the availability and use of mobile phones have grown exponentially globally and in Cambodia. In the Sihanouk Hospital Centre of Hope(SHCH) in Cambodia about half of all tuberculosis patients referred out to peripheral health facilities for TB treatment initiation or continuation were lost to contact after referral ranging from 19 to 69% between 2008 and 2013. To address this, we implemented a mobile phone-based patient tracking intervention. Here, we report the number and propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 6 publications
2
23
0
1
Order By: Relevance
“…Similar results were also found in Asia. In Cambodia, by contacting 109 patients who were referred for tuberculosis treatment, 97% attended the treatment (Choun et al, 2017). Although that study was not conducted on diabetic patients, this report is consistent with our results and indicates that mHealth interventions can be effective in enhancing treatment adherence.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were also found in Asia. In Cambodia, by contacting 109 patients who were referred for tuberculosis treatment, 97% attended the treatment (Choun et al, 2017). Although that study was not conducted on diabetic patients, this report is consistent with our results and indicates that mHealth interventions can be effective in enhancing treatment adherence.…”
Section: Discussionsupporting
confidence: 89%
“…ICT infrastructure plays a critical role for TB management, particularly in coordinating case monitoring, treatment initiations, and referral mechanisms to ensure treatment adherence and completion [29]. This further corroborates findings by Choun et al (2017), who demonstrated that mobile phones with internet services facilitate TB diagnosis, referrals, and treatment monitoring among TB patients, and led to marked reductions in mortality rates among sampled patients [10]. Consequently, SMS technology and other internet-enabled treatment reminder tools provide opportunities to improve vaccination rates, strengthen service delivery, and track follow-up.…”
Section: Tuberculosis Incidencesupporting
confidence: 74%
“…It boosts health literacy and empowers individuals to live healthy lives. Choun et al (2017) demonstrated how mobile phone technology facilitated TB diagnosis, treatment completion, and referrals among TB patients at the Sihanouk Hospital Center of Hope, Cambodia. This mHealth strategy led to 12% decreases in mortality rates among sampled patients [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to its large user base in India,23 mobile phones have caught the attention of public health researchers as effective tools to enhance the impact of public health programme. Mobile phone reminders either by voice call or short message services have been explored to enhance TB treatment adherence and improve the outcomes in India, Thailand, Africa, Pakistan, Malaysia and Cambodia 24–29. Smartphone apps found to be effective in data management, better patient referral and improving treatment adherence and outcome for patients with TB in India and other countries 30–32.…”
Section: Discussionmentioning
confidence: 99%